Comparative post rumen nutrient availability from naturally fermented and urea-treated wheat straw - MAKHDOOMI, A A.; BAKSHI, M P S; LANGAR, P N (The Indian Journal of Animal Sciences, 2013)
Urea (3.5%; W/W) and wheat-straw mixture (UWS), after processing by (i) sun-drying. (ii) open stacking for 6- or 9-day-natural fermentation with 40 and 70% moisture, and (iii) conventional 28 - day urea (4%) treatment at 45% moisture . was evaluated for nutrient availability in the abomasum of buffalo. For comparison a control diet of a urea-free concentrate supplement and unprocessed straw was also evaluated. To an individual buffalo different complete diets were fed daily with 2 kg available green fodder arid 30 g each of mineral-salt mixture. Stacking for 28 days resulted in more organic matter less than when stacking period of 8- to 9- day was used in natural fermentation process. Under the diet containing naturally fermented straw preparation (obtained with 70% moisture) the rate of passage of digesta rumen fluid dilution and outflow rates had created favourable rumen reactions than those under the diets containing sun-dried or urea-treated straw preparations. As a result of favourable rumen reactions under the above fermented straw diet, the nutrient passage at the abomasum was comparable to that under the control diet. The next best passage of total water-soluble sugars: tricolour acetic acid, perceptible protein and non-ammonia-N at the abomasum was observed under a diet containing a straw preparation naturally fermented with 40% moisturise for 9 days. These results suggested that in a stacking process used for upgrading cereal crop residue(s) as fodder both the moisture level and duration of treatment influenced the nutrient conservation and availability at the abomasum for which the natural fermentation appeared to be the most suitable.